2022
DOI: 10.1101/2022.01.06.475282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mild SARS-CoV-2 infection in rhesus macaques is associated with viral control prior to antigen-specific T cell responses in tissues

Abstract: SARS-CoV-2 primarily replicates in mucosal sites, and more information is needed about immune responses in infected tissues. We used rhesus macaques to model protective primary immune responses in tissues during mild COVID-19. Viral RNA levels were highest on days 1-2 post-infection and fell precipitously thereafter. 18F-fluorodeoxyglucose (FDG)-avid lung abnormalities and interferon (IFN)-activated myeloid cells in the bronchoalveolar lavage (BAL) were found on days ~3-4. Virus-specific effector CD8 and CD4 T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 88 publications
5
22
0
Order By: Relevance
“…However, the kinetics of SARS-CoV-2 replication in rhesus macaques means that memory T cells are unlikely to have an opportunity to expand and traffic to the lung within the window of active viral replication. Even in naive animals, viral control is achieved prior to the development of tissue-specific SARS-CoV-2 T cell responses, and several studies have now shown that depletion of T cells in the macaque model only modestly affects viral control, especially in the setting of high levels of neutralizing antibodies (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…However, the kinetics of SARS-CoV-2 replication in rhesus macaques means that memory T cells are unlikely to have an opportunity to expand and traffic to the lung within the window of active viral replication. Even in naive animals, viral control is achieved prior to the development of tissue-specific SARS-CoV-2 T cell responses, and several studies have now shown that depletion of T cells in the macaque model only modestly affects viral control, especially in the setting of high levels of neutralizing antibodies (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, S-specific (IFNγ + /TNFα + ) CD4 + and CD8 + T-cells from BAL could be separated into circulating CD69 - CD103 - and tissue-resident memory (Trm) CD69 + CD103 +/- subsets (Zheng and Wakim, 2021) (Figure 5, E and F for CD4 + T-cells and Figure 5, G and H for CD8 + T-cells, respectively). An additional subset of presumably tissue-resident S-specific CD4 + and CD8 + T-cells was identified as CD69 - CD103 + and has been previously detected in SARS-CoV-2-infected RMs (Nelson et al, 2022). Circulating CD69 - CD103 - S-specific CD4 + and CD8 + T-cells were detectable in BAL on day 9 pi and were prominent until day 14, representing about 60% of the S-specific T-cells on this day (Figure 5, F and H).…”
Section: Resultsmentioning
confidence: 70%
“…). An additional subset of presumably tissue-resident S-specific CD4 + and CD8 + T-cells was identified as CD69 -CD103 + and has been previously detected in SARS-CoV-2-infected RMs (Nelson et al, 2022). Circulating CD69 -CD103 -S-specific CD4 + and CD8 + Tcells were detectable in BAL on day 9 pi and were prominent until day 14, representing about 60% of the S-specific T-cells on this day (Figure 5, F and H).…”
Section: T-cells Respectivelymentioning
confidence: 68%
“…The relatively mild course of SARS-CoV-2 infection in macaques [26] might explain this different pattern of activation marker expression. The activation of these innate immune-cells could possibly contribute to the eradication of SARS-CoV-2 that was indeed shown to occur prior to onset of antigen specific T cell responses [27] . Interestingly, we observed that both increased TSPO activity as well as DC activation persisted for at least 30 days pi, despite clearance of the virus by day 10 pi.…”
Section: Discussionmentioning
confidence: 99%